2010
DOI: 10.1089/thy.2010.0047
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Hypocalcemia After Thyroidectomy for Graves' Disease

Abstract: Patients with Graves' disease are more likely to require increased dosages of calcium as well as experience tetany postoperatively than patients undergoing total thyroidectomy for other indications. This suggests that patients operated upon for Graves' disease warrant close followup as both inpatients and outpatients for signs and symptoms of hypocalcemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
2
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 13 publications
6
64
2
3
Order By: Relevance
“…The Chovstek sign is elicited by tapping the facial nerve in the preauricular area and observing for facial contractions; Trousseaus sign by induction of carpal spasm upon inflation of blood pressure cuff above the systolic value. 8,9 The best way to reserve the PT function is the deliberate identification of them and safeguarding its blood supply. In a cadaveric study, 77% of the superior PT was at the cricothyroid junction, intimately associated with the RLN.…”
Section: Resultsmentioning
confidence: 99%
“…The Chovstek sign is elicited by tapping the facial nerve in the preauricular area and observing for facial contractions; Trousseaus sign by induction of carpal spasm upon inflation of blood pressure cuff above the systolic value. 8,9 The best way to reserve the PT function is the deliberate identification of them and safeguarding its blood supply. In a cadaveric study, 77% of the superior PT was at the cricothyroid junction, intimately associated with the RLN.…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14][15] The old literature, in fact, described some cohorts as "normocalcemic", while more careful inspection has shown that these patients were intermittently normocalcemic. [16][17][18][19][20] The incidence of permanent hypocalcaemia which required calcium supplementation was more accurate with serial calcium estimation than the intact parathyroid hormone (iPTH) levels obtained after total thyroidectomy. The serial calcium level estimations are more predictable and coast effective than intact parathyroid hormone (i PTH) estimation in predicting long term postoperative hypocalcaemia after total/near total thyroidectomy.…”
Section: Discussionmentioning
confidence: 99%
“…A major cause of postoperative hypoparathyroidism is inadvertent injury during surgery, such as mechanical or thermal trauma, gland devascularization or incidental parathyroidectomy (23)(24)(25). There have been many studies that have reported the surgical risk factors of postthyroidectomy hypocalcemia, such as re-operation, large goiter (25), Graves' disease (27), and thyroid cancer (28). There have also been reports of clinical predictors of postoperative hypocalcemia, such as calcium levels being less than 1.88 mmol/L (reading taken 24 h after surgery), and the inability to identify more than one PTG during surgery (25).…”
Section: Syndromes Of Hypoparathyroidism After Total Thyroidectomymentioning
confidence: 99%